Caracterización de flavonoides y actividad antimicrobiana del extracto metanólico de hojas de Luma chequen (Molina) A. Gray - Fernández-Rebaza, Gustavo Adolfo (2024)
Introduction. The research of new alternatives to antimicrobial resistance has led to the exploration of medicinal plant extracts. Luma chequen has antimicrobial activity, but the secondary metabolites have not been identified. Objective. Characterize the chemical structures of flavonoids and to evaluate the antimicrobial activity of the methanolic extract of Luma chequen (Molina) A. Gray leaves. Methods. The methanolic extract of the leaves was prepared and its solubility with solvents of increasing polarity was evaluated, then a phytochemical screening was carried out, identifying different secondary metabolites. Thin layer chromatography (TLC) used standards and developers. The chemical structures of the flavonoids present in the methanolic extract were characterized by UV-Visible spectroscopy and displacement reagents. The antimicrobial activity was determined by the agar-well diffusion assay against Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas  aeruginosa. Results. The extract was soluble in solvents of medium polarity. TLC detected the presence of phenolic compounds, flavonoids and alkaloids. UV-Visible spectroscopy identified five flavonoid chemical structures, including four flavones and one aurone. The extract presented broad-spectrum antimicrobial activity against gram-positive and gram-negative bacteria at concentrations of 50 to 100 mg/mL. Conclusions. Different secondary metabolites were detected by phytochemical screening and chromatography; in addition, five flavonoid structures were characterized by UV-visible spectrophotometry and diagnostic reagents. Likewise, the extract presented antimicrobial activity against Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli.